Mosquito and tick repellency of two Anthemis essential oils from Saudi Arabia - Hasan Soliman Yusufoglu; Nurhayat Tabanca; Ulrich R. Bernier; Andrew Y. Li; Mohammed Ayman Salkini; Saleh Ibrahim Alqasoumi; Betul Demirci (Saudi Pharmaceutical Journal, 2018)
The essential oils (EOs) of Anthemis melampodina (Am) and Anthemis scrobicularis (As) (Asteraceae) were extracted from the aerial parts of the plants by hydrodistillation, and their chemical compositions were analyzed using GC-FID and GC-MS. Fifty-six components representing 85.5% of the oil composition of Anthemis melampdina were identified, and the major components were α-pinene (17.1%) and β-eudesmol (13.8%). Forty-one components representing 86% of the oil composition of Anthemis scrobicularis were identified, and the major component was β-eudesmol (12.8%). Laboratory bioassays were conducted to determine repellency of Am and As EOs against the yellow fever mosquito Aedes aegypti L. and the lone star tick Amblyomma americanum L. The minimum effective doses (MEDs) of the Am and As EOs against mosquitoes were 0.187 ± 0.000 and 0.312 ± 0.063 mg/cm2 respectively, which were significantly higher than that of DEET (0.023 ± 0.000 mg/cm2) in human-based repellent bioassays. The As EO was more repellent than Am EO against nymphal ticks but was less effective than DEET in vertical paper bioassays. Keywords: Anthemis melampodina, Anthemis scrobicularis, Natural repellents, Aedes aegypti, Amblyomma americanum